2020
DOI: 10.1155/2020/3251275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure to Famine during Early Life on Risk of Metabolic Syndrome in Adulthood: A Meta-Analysis

Abstract: Background. Emerging studies have explored the association between the famine exposure during early life and the risk of the metabolic syndrome, and the results remain controversial. This meta-analysis was performed to summarize the famine effects on the prevalence of metabolic syndrome (MetS) in adulthood. Materials and Methods. We searched the PubMed, Web of Science, Embase, ScienceDirect, and Chinese National Knowledge Infrastructure for relevant studies up to December 2019. Pooled odd ratios (ORs) with 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
(47 reference statements)
3
18
0
2
Order By: Relevance
“…Compared with a non-exposed group, early-life famine exposure significantly increased the risk of MetS in women only. 88 However, most studies were conducted in China where families may have preferentially allocated food and other resources to sons at the expense of daughters during the famine due to a culture of ‘son preference’. 89 Malnutrition severity may thus explain increased NCD risk in women.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with a non-exposed group, early-life famine exposure significantly increased the risk of MetS in women only. 88 However, most studies were conducted in China where families may have preferentially allocated food and other resources to sons at the expense of daughters during the famine due to a culture of ‘son preference’. 89 Malnutrition severity may thus explain increased NCD risk in women.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese famine from 1959 to 1961 is considered to be one of the largest and most severe famines, which provides an opportunity to explore the association between fetal famine exposure and health outcomes. Previous studies indicated that exposure to famine during early life may increase obesity, hypertension, diabetes and other diseases in adulthood [10][11][12][13]16,19,20,[22][23][24][25][26]28,30,32,33,[36][37][38][39][40][41][42]. Regarding obesity, some studies focused their attention on the fetal exposure to famine and BMI or WC in some regions of China or foreign countries [13,19,20,30,31,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they failed to recognize methodological problems discussed above, especially uncontrolled age differences between famine births and post-famine births in Chinese famine studies. [6][7][8][9][10][11][12] This shows how meta-analysis of observational studies would generate misleading results unless careful examination of study methods is carried out. 21,22 It is important to keep in mind using meta-analysis as an exploratory and comparative tool rather than a tool of producing 'precise' results especially for observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple meta-analyses have been conducted to summarize long-term impacts of the Chinese famine and other famines on health outcomes. [6][7][8][9][10][11][12] These individual studies and meta-analyses claimed increased risks of adverse health outcomes with prenatal famine exposure. Many reviews and commentaries therefore concluded that famine exposure is a major driver for the current T2D epidemic in China and will contribute to an increased risk of T2D in future generations.…”
Section: Introductionmentioning
confidence: 99%